2022
DOI: 10.1371/journal.pone.0275933
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the quality of antenatal care and pregnancy outcomes in a tertiary hospital in Ghana

Abstract: Background Antenatal care (ANC) is imperative to decreasing adverse pregnancy outcomes and their related maternal mortality. However, in sub-Saharan Africa, increases in ANC coverage have not correlated well with improved maternal and fetal outcomes suggesting the quality of ANC received could be the missing link. This study assessed ANC quality and its effect on adverse pregnancy outcomes among women who delivered at Komfo Anokye Teaching Hospital. Methods A cross-sectional study was conducted among women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…On the other hand, one could point to the insufficient coverage of ANC or inadequate ANC visits to allow for better pregnancy monitoring, increasing the chance of emergency CS. A recent study by Amponsah-Tabi et al in Ghana found the quality of ANC was significantly associated with pregnancy outcomes which included anaemia during pregnancy, pre-eclampsia with severe features or delivering a low birth weight baby 26…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one could point to the insufficient coverage of ANC or inadequate ANC visits to allow for better pregnancy monitoring, increasing the chance of emergency CS. A recent study by Amponsah-Tabi et al in Ghana found the quality of ANC was significantly associated with pregnancy outcomes which included anaemia during pregnancy, pre-eclampsia with severe features or delivering a low birth weight baby 26…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, access to emergency caesarean delivery is available only at hospitals and specialty clinics [ 11 , 12 ], and still the birth-related complications and deaths are high [ 9 ]. Because of prolonged labour, dysfunctional labour, and the high risk of induction of labour, women with advanced maternal age (>35 years old), inadequate antenatal care visits, and being nulliparous were at risk for emergency caesarean delivery [ 13 17 ]. In Ethiopia, the early neonatal adverse event after emergency caesarean delivery is 26.7% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor quality and inadequate utilization of ANC services during pregnancy may increase the risk of preventable adverse pregnancy outcomes but how these collectively influence these outcomes remain understudied. Though some studies in Ghana including [ 21–23 ] have assessed the individual effect of ANC components (that is, timing, frequency and content) on pregnancy outcomes, none but one [ 24 ] has investigated the joint effect of these variables. More especially, little is documented regarding the protective effect of adequate utilization of the recommended eight or more ANC contacts on adverse pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%